Control of anterior GRadient 2 (AGR2) dimerization links endoplasmic reticulum proteostasis to inflammation. Issue 6 (30th April 2019) - Maurel, Marion; Obacz, Joanna; Avril, Tony; Ding, Yong‐Ping; Papadodima, Olga; Treton, Xavier; Daniel, Fanny; Pilalis, Eleftherios; Hörberg, Johanna; Hou, Wenyang; Beauchamp, Marie‐Claude; Tourneur‐Marsille, Julien; et al.
Abstract: Anterior gradient 2 (AGR2) is a dimeric protein disulfide isomerase family member involved in the regulation of protein quality control in the endoplasmic reticulum (ER). Mouse AGR2 deletion increases intestinal inflammation and promotes the development of inflammatory bowel disease (IBD). Although these biological effects are well established, the underlying molecular mechanisms of AGR2 function toward inflammation remain poorly defined. Here, using a protein–protein interaction screen to identify cellular regulators of AGR2 dimerization, we unveiled specific enhancers, including TMED2, and inhibitors of AGR2 dimerization, that control AGR2 functions. We demonstrate that modulation of AGR2 dimer formation, whether enhancing or inhibiting the process, yields pro‐inflammatory phenotypes, through either autophagy‐dependent processes or secretion of AGR2, respectively. We also demonstrate that in IBD and specifically in Crohn's disease, the levels of AGR2 dimerization modulators are selectively deregulated, and this correlates with severity of disease. Our study demonstrates that AGR2 dimers act as sensors of ER homeostasis which are disrupted upon ER stress and promote the secretion of AGR2 monomers. The latter might represent systemic alarm signals for pro‐inflammatory responses. Synopsis: This study provides molecular insights into the anterior gradient 2 (AGR2) mode of action in the endoplasmic reticulum (ER) with an emphasis on the regulation of AGR2 dimers. Dysregulation of AGR2 dimer formation leads to inflammation as seen in inflammatory bowel disease (IBD) and Crohn's disease. AGR2 is a chaperone involved in the regulation of protein quality control in the ER. We have developed and used a novel cellular protein‐protein interaction screen to identify cellular regulators of AGR2 dimerization. We identify specific enhancers, including TMED2, and inhibitors of AGR2 dimerization, that control AGR2 functions. Modulation of AGR2 dimer formation, whether enhancing or inhibiting the process, yields pro‐inflammatory phenotypes, through either autophagy‐dependent processes or secretion of AGR2, respectively. In IBD and specifically in Crohn's disease, the levels of AGR2 dimerization modulators are selectively deregulated, and this correlates with severity of disease. AGR2 dimers act as sensors of ER homeostasis which are disrupted upon ER stress and promote the secretion of AGR2 monomers. The latter might represent systemic alarm signals for pro‐inflammatory responses. Abstract : This study provides molecular insights into the anterior gradient 2 (AGR2) mode of action in the endoplasmic reticulum (ER) with an emphasis on the regulation of AGR2 dimers. Dysregulation of AGR2 dimer formation leads to inflammation as seen in inflammatory bowel disease (IBD) and Crohn's disease.